Management Union (1960)
Names given from left to right: Brian Childs, Dennis Maher, Don Wasson, Bonnie Lamb, Mike (illegible), Tom (illegible), Pete Dorn, Dr. P.H. Overmeyer, Wayne Griffin, William Schwern, Edward A. Mukai, Joan Borame, Gennaro F. Filice, Mollie Fossatti, Carol A. Lawrence